The diatom genus Gomphoneis Cleve (Bacillariophyceae) from Lake Baikal, Russia - Kociolek, John P.; Kulikovskiy, Maxim S.; Solak, Cüneyt N. (Phytotaxa, 2013)
We describe 22 new species of Gomphoneis, and report several previously described taxa, from historical and recently made collections from Lake Baikal, Russia. We use light microscopy to document all taxa, and scanning electron microscopy to illustrate several of the species from the lake. All of the species present in Lake Baikal are part of the Elegans subgroup of the genus. Despite previous reports, we could find no representatives of the Herculeana subgroup in Baikal. We provide comparisons between the taxa, and document variability in the features found in the species. Two groups within the Elegans subgroup are present; most have 4 (or more) stigmoids, while a minority of the species lack stigmoids. We suggest that the species in Lake Baikal have two origins; one from the West, where an arc of related species spans Mongolia, NW China to Macedonia, and the second from western North America. Radiation of the two groups has resulted in species flocks. The number of Gomphoneis species in Lake Baikal is the largest number of species of the genus anywhere in the world.